Involving prisoners in action research to improve palliative care: findings from the 'both sides of the fence' study. Issue 3 (1st September 2016) - Turner, Mary; Peacock, Marian; Varey, Sandra; Froggatt, Katherine; Payne, Sheila; Gibson, Bob; Scott, Gill; Fletcher, Andrew
Abstract : Introduction: With more than 12, 000 older prisoners in the UK, deaths in custody are increasing, 1 as is the need for palliative care. The 'Both sides of the fence' study used action research methodology in one prison with a high population of older offenders. Interviews with staff and prisoners in Phase 1 provided the foundation for action cycles that took place in Phase 2; this paper reports action cycles directly involving older prisoners. Aim(s) and method(s): The aim was to engage with prisoners in making meaningful improvements to palliative care. First, an Older Prisoners Group (OPG) was established and facilitated by prison staff and researchers. The OPG met bi-monthly, with smaller groups of prisoners working on tasks between meetings. OPG members created an information leaflet on planning for the end of life in prison. They were also involved in the development of an Older Prisoners Unit (OPU) to reduce intimidation of vulnerable older prisoners by younger offenders. Results: One thousand copies of the leaflet were produced for use by prisoners in the research site and other prisons. The OPU is a protected environment for prisoners over 50, with medication lockers in each room; prisoners in the OPU have reported feeling safer and less stressed. They also reported increased self-esteem through their involvement in the research. Conclusion(s): Involving prisoners in action research can have positive benefits for both prisoners and staff. Sustainability of these benefits will be achieved by the continuation of the OPG after the end of the study. Reference: Prison Reform Trust.Bromley Briefings Prison Factfile, Autumn 2015. London: Prison Reform Trust; 2015.